TELEVISION GENRES AND THEIR ROLE IN SHAPING PUBLIC OPINION - Zokirova Shaxzoda Nodirjon qizi (Bright Mind Publishing, 2025)
This article examines the role of television genres in shaping public opinion. It explores the characteristics of informative, analytic, and publicistic genres, highlighting how they influence audience perception through rhetorical strategies and communicative techniques. The study analyzes news broadcasts, talk shows, and other TV formats to demonstrate the mechanisms of persuasion and their socio-cultural impact.
Keywords: Television, genres, public opinion, informative programs, analytic programs, publicistic genres, media influence.